Le fratture di avambraccio - Berizzi, A.; Angelini, A.; Pala, E.; Biz, C.; Trovarellli, G.; Ruggieri, P. (Lo Scalpello - Journal, 2018)
FRACTURES OF THE FOREARM Fractures of the forearm in the growing skeleton in a common event, accounting for 10% of the overall fracture and at the third place for long bone fractures. Most of these fractures present a simple line. There are several classification but the most widely use is the anatomo-radiological one. The majority of the fracture require closed reduction and immobilization in a long arm cast, with the elbow flexed at 90°, since residual defect that can occur are well tolerate. Under the age of nine angulation deformities lesser than 15° have the possibility to remodell completely. Over the age of nine the toleration is lower than 10°. The time of immobilization has to be at least of 8 weeks, in order to reduce the high risk of refracture. The surgical management of these fracture must to be reserved in case of unstable fractures or impossibility to gain good reduction by closed means. The best surgical solution nowadays is stabilization with elastic stable intramedullary nail. Open reduction and plate osteosynthesis must to be reserved for late adolescent, very near to skeletal maturity. External fixation has limited indication, expecially in politrauma and very high grade of open fractures.